Supervisi Pendidikan Islami: Mengintegrasikan Konsep Hisbah Dengan Teori Transformational Leadership - Qathrunnada, Nabila; Thohir, Muhammad; Sahudi, Sahudi (JURNAL MANAJEMEN PENDIDIKAN, 2026)
ISLAMIC EDUCATION SUPERVISION: INTEGRATING THE CONCEPT OF HISBAH WITH TRANSFORMATIONAL LEADERSHIP THEORY This research and journal aim to analyze the implementation of Islamic education supervision by integrating the concept of hisbah and transformational leadership theory at MI Darul Ulum Tambakrejo, Sidoarjo. The research employs a qualitative approach with a case study design. Data for this study were collected through in-depth interviews, observation, and documentation, involving the school principal and teachers as the primary sources of information. This research indicates that the educational supervision at MI Darul Ulum is not only evaluative in nature but also focuses on guidance based on Islamic values such as amr ma’ruf nahi munkar (enjoining what is right and forbidding what is wrong), justice, and exemplary conduct (keteladanan). The school principal plays the role of a muhasib with a function of moral supervision, as well as a transformational leader who motivates and inspires teachers. The implemented transformative Islamic supervision contributes to the enhancement of teachers' professionalism and spirituality. However, some constraints were found, such as limited time and initial resistance to the supervision's early implementation. This supervision model has the potential to become an ideal approach for Islamic educational institutions in strengthening overall learning quality.